Recharacterizing restructuring : Law, distribution and gender in market reform. - Rittich, K. (BRILL, 2002)
Since the early-1990s, market-centred economic reforms have been implemented in a wide range of developing and transitional countries under the auspices of the international financial institutions. Whether or not they deliver the priomised prosperity, they appear to be associated with widening economic inequality as well as disadvantage for particular social groups, among them women and workers. ""Recharacterizing Restructuring"" argues that such effects are neither temporary nor accidental. Instead, efforts to promote growth through greater efficiency inevitably engage distributive concerns